Simulation of Auger decay dynamics in the hard X-ray regime: HCl as a showcase. Issue 11 (2nd March 2022) - Goldsztejn, G.; Guillemin, R.; Marchenko, T.; Travnikova, O.; Céolin, D.; Journel, L.; Simon, M.; Piancastelli, M. N.; Püttner, R.
Abstract : 2-D core-electron spectroscopy: resolving excitation and relaxation pathways. Abstract : Auger decay after photoexcitation or photoemission of an electron from a deep inner shell in the hard X-ray regime can be rather complex, implying a multitude of phenomena such as multiple-step cascades, post-collision interaction (PCI), and electronic state-lifetime interference. Furthermore, in a molecule nuclear motion can also be triggered. Here we discuss a comprehensive theoretical method which allows us to analyze in great detail Auger spectra measured around an inner-shell ionization threshold. HCl photoexcited or photoionized around the deep Cl 1s threshold is chosen as a showcase. Our method allows calculating Auger cross sections considering the nature of the ground, intermediate and final states (bound or dissociative), and the evolution of the relaxation process, including both electron and nuclear dynamics. In particular, we show that we can understand and reproduce a so-called experimental 2D-map, consisting of a series of resonant Auger spectra measured at different photon energies, therefore obtaining a detailed picture of all above-mentioned dynamical phenomena at once.